2011
DOI: 10.5604/17322693.931085
|View full text |Cite
|
Sign up to set email alerts
|

The role of ghrelin in the organism

Abstract: Ghrelin was discovered in 1999 as an endogenous ligand of the growth hormone secretagogue receptor (GHS-R). About 60-70% of ghrelin in the blood is released from oxyntic cells (X/A-like cells) of the stomach body and fundus. Ghrelin acts via interactions with specific receptors located, for example, in the hypothalamus, pituitary gland, pancreas, kidneys, myocardium, blood vessels, adipose tissue, ovaries and placenta. Ghrelin is directly related to the control of energy balance through appetite stimulation, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
0
17
0
8
Order By: Relevance
“…During the period of food deprivation the level of ghrelin in blood plasma increases while the level of leptin decreases. This process reverses during food intake [1,2,7,14]. The quality of food is of importance.…”
Section: Overview and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the period of food deprivation the level of ghrelin in blood plasma increases while the level of leptin decreases. This process reverses during food intake [1,2,7,14]. The quality of food is of importance.…”
Section: Overview and Discussionmentioning
confidence: 99%
“…Ghrelin and leptin are peptide hormones which are antagonistic towards each other and thus regulate the energy balance of the body [1][2][3]. Ghrelin, whose secretion intensifies as the negative energy balance increases, augments the feeling of hunger and reduces energy expenditure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Three hormones encoded by the ghrelin gene have been discovered in recent years, namely obestatin, de-acylated ghrelin, and acylated ghrelin, also known as bioactive peptides. In previous trials, it was well established that ghrelin displays anti-inflammatory activities (15). Furthermore, the data obtained in these trials showed that hormones encoded by the ghrelin gene are synthesized in the pancreas, emphasizing the protective activity on the pancreas in general (16).…”
Section: Discussionmentioning
confidence: 99%
“…It stimulates appetite, increases hydrochloric acid secretion, enhances gastrin secretion, regulates gastrointestinal motility, and protects the gastric mucosa. Its effect is not limited to the gastrointestinal tract, it affects the gonads, insulin secretion, the cardiovascular system (inter alia, by suppressing cardiomyocytes and vascular endothelial cells) [38]. Ghrelin decreases arterial pressure and increases the cardiac index [2].…”
Section: Hormones Of the Gastrointe-stinal Tract And Secretion Cellsmentioning
confidence: 99%